Photocatalytic Selective Oxidation of Organic Compounds in Graphitic Carbon Nitride Systems: A Review - Stroyuk, A. L.; Raevskaya, A. E.; Kuchmy, S. Ya (Theoretical and Experimental Chemistry, 2019)
Recent work is reviewed concerning photocatalytic systems derived from graphitic carbon nitride (GCN) for the selective oxidation of various organic compounds including saturated and unsaturated hydrocarbons, alcohols, and organic sulfides. Examples are given for oxidative coupling of a series of organic compounds with the formation of carbon–nitrogen and carbon–carbon bonds as well as cyclization. The properties of various GCN samples were examined, including bulk, mesoporous, layered, and individual materials as well as samples modified with organic compounds, samples doped with metals and nonmetals, and GCN-derived composite materials. The outlook for future research in this field is given at the conclusion.
CRIS-Team Scopus Importer:2019-08-30
Keywords: cyclization reactions; graphitic carbon nitride; organic compounds; oxidation; oxidative coupling; photocatalysis